Malabsorption mayhem: A Vitamin K story in trauma care - Awale, Rupali; Singh, Amit; Chandra, Dinesh; Arora, Riddhima (Indian Journal of Case Reports, 2026)
A young adult male presented with persistent vomiting and a history of recent trauma and abdominal surgery. He was found to have significant coagulopathy, evidenced by marked prolongation of prothrombin time and activated partial thromboplastin time. Laboratory and clinical evaluation revealed multifactorial Vitamin K deficiency, likely due to malnutrition, malabsorption, and ongoing physiological stress. Prompt administration of Vitamin K resulted in rapid correction of coagulation parameters, facilitating safe surgical intervention without excessive intraoperative bleeding. Despite aggressive surgical and supportive management, the patient’s course was complicated by recurrent infections and ultimately fatal septic shock. This case underscores the importance of early recognition of Vitamin K deficiency in trauma and surgical patients, especially those with risk factors for malnutrition or gastrointestinal compromise. Timely correction of coagulopathy is vital to minimize perioperative risks and improve clinical outcomes